Cytokinetic study of uninfected agarwood branch ethanolic extract on breast cancer cells - Abbas, Phirdaous; Hashim, Yumi Zuhanis Has-Yun; Amid, Azura (Malaysian Society for Molecular Biology and Biotechnology, 2017)
Breast cancer is the most common malignancy in women with over 500,000 global death toll annually. Ethnopharmaceutical practices provide evidences of Aquilaria spp. as traditional treatment for numerous illness. This study intended to look into the cytotoxic kinetics of uninfected agarwood branch ethanolic extract from Aquilaria subintegra against MCF-7 breast cancer cell line that could help grasp the effect and provide baseline towards development of agarwood-based therapeutics. Extract was subjected to a series of kinetic studies in order to investigate the growth rate, death rate, doubling time and death time of MCF-7 between the treated and control groups. Results obtained indicated that the extract lowered the growth rate from 0.0421 h-1 to 0.0158 h-1 and stretched the doubling time from 16.4 hours to 43.8 hours. Death rate was escalated from 0.0058 h-1 to 0.0563 h-1. Closer inspection on the population density images revealed that the extract-treated MCF-7 cells showed abnormal appearance with blebs, volume reduction, cell shrinking and loss of cell-cell contact. These discoveries implied that agarwood uninfected branch ethanolic extract altered the kinetics of MCF-7 cells and additional study should be made to substantiate the hypothesis and elucidate the effects against cancer.